حكم صنع التمثال من الثلج على شكل صورة إنسان أو حيوان: The Law of Making Sculptures Out of the Snow in the Shape of Human or Animals - Ayrat Aymetov (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the law of making snow sculptures in the form of images of living things, whether they resemble human or animal images from the perspective of Islamic law. This research uses inductive-deductive method. The results showed that, first, making snow sculptures for adults with complete limbs and clear features is prohibited and not allowed because it is included in the general prohibition on making sculptures from living things, and it needs to be reminded that making statues from living things the perishable are less restrictive than making a permanent statue; secondly, the making of a snow sculpture with incomplete organs - so as not to be left behind with the loss of its life - with a head by an adult, the more important thing is to refrain from doing this, due to its resemblance to the making of statues in general which has a clear prohibition; third, if the statue bears no resemblance to clear facial features, for example it does not have eyes, nose or mouth, but appears in a three-dimensional form without features, then the strongest opinion is that it is permissible, because there is no prohibition in that regard; fourthly, as for children, to play and have fun, then that is lawful for them, and pictures are permissible for children and not permissible for adults.